Un tipo ideal de planta de yuca para rendimiento máximo [conjunto audiotutorial] - Cock, James H.; Domínguez O., Carlos E.; Ceballos L., Luis Fernando; Arregocés, Oscar (International Center for Tropical Agriculture, 1979)
This audiotutorial unit (cassette, printed script, 76 color slides, study guide, self-evaluation test), prepared by the Communications Support Unit at CIAT, is available for use with a manually or automatically synchronized slide projector/cassette tape reccorder. Each unit is a vailabIe from the Distribution Office at a cost of US$ 50; photocopies of the study guide alone can be obtained from the Cassava Information Center. The objective of this unit is to present some of the results of research conducted by the physiology Section of CIATs Cassava Program. First the LAI and the morphological components of the same (leaf size, life and no./unit area) are studied; then growth rate or rate of DM accumulation and dependence on leaf area are analyzed. Based on a mathematical model for the development of a cassava plant, it is possible to predict the effects on yield of variations in one or more of its components, thus determining what could be considered as an ideal plant type. (CIAT)